Metagenomic and Metabolomic Insights Into the Mechanism Underlying the Disparity in Milk Yield of Holstein Cows - Amin, Abdulmumini B.; Zhang, Lei; Zhang, JiYou; Mao, Shengyong (Frontiers in Microbiology, 2022)
Abstract This study was conducted to investigate the metabolic mechanism underlying the disparity in the milk yield of Holstein cows. Eighteen (18) lactating Holstein cows in their 2nd parity and 56 (± 14.81 SD) days in milking (DIM) were selected from 94 cows. Based on the milk yield of the cows, they were divided into two (2) groups of 9 cows each, the high milk yield group (HP) (44.57 ± 2.11 kg/d) and the low milk yield group (LP) (26.71 ± 0.70 kg/d). The experimental cows were fed the same diet and kept under the same management system for more than 60 days. Rumen metagenomics revealed that 2 Archaea genera, 1 Bacteria genus, 8 Eukaryota genera, and 2 Virus genera differ between the HP and LP groups. The analysis of metabolites in the rumen fluid, milk, and serum showed that several metabolites differed between the HP and LP groups. Correlation analysis between the predominant microbiota and milk yield-associated metabolites (MP-metabolites) revealed that 4 Bacteria and 2 Eukaryota genera have a positive relationship with MP-metabolites. Pathway enrichment analysis of the differential metabolites revealed that 5 pathways were enriched in all the samples (2 pathways in the milk, 2 pathways in the serum, and 1 pathway in the rumen fluid). Further investigation revealed that the low milk yield observed in the LP group might be due to an upregulation in dopamine levels in the rumen fluid and milk, which could inhibit the release of prolactin or suppress the action of oxytocin in the udder resulting in reduced milk yield. On the other hand, the high milk yield in the HP group is attributed to an upregulation in citrulline, and N-acetylornithine, which could be used as substrates for energy metabolism in the citric acid cycle and ultimately gluconeogenesis. Keywords: Holstein cow, Milk yield, Rumen metagenomics, Metabolomics, Citric acid cycle